PELAKSANAAN PEMBERIAN BANTUAN HUKUM BAGI MASYARAKAT YANG TIDAK MAMPU DALAM PANDANGAN HUKUM ISLAM (Study Kasus di Lembaga Bantuan Hukum Pancaran Hati Cirebon - Akhmad Shodikin; Didi Sukardi; Lailiyah Lailiyah (Mahkamah : Jurnal Kajian Hukum Islam, 2022)
This study aims to determine the implementation of providing legal aid for the poor at the Pancaran Hati Cirebon Legal Aid Institute (LBH) and the views of Islamic law on providing legal aid for underprivileged communities at the Pancaran Hati Cirebon Legal Aid Institute (LBH). The research method used is qualitative research. Qualitative research that describes phenomena or research facts as they are. This type of research is an empirical juridical research that examines legal provisions. Research data obtained from interviews and documentation. The implementation of providing legal aid for underprivileged communities at the Pancaran Hati Cirebon Legal Aid Institute (LBH) plays a very important role in providing legal aid to underprivileged communities seeking justice. To obtain legal assistance, namely by submitting a written application containing the identity of the applicant (KK or KTP), attaching an SKTM (certificate of incapacity) and briefly describing the case, submitting case documents and surveys to the home location. Budget funds in providing legal assistance from the BPHN Ministry of Law and Human Rights, the Government of West Java Legal Bureau and the Government of West Java's Kuningan Law Bureau. The duties and authorities of the Legal Aid Institute (LBH) Pancaran Hati Cirebon are to provide litigation and non-litigation legal assistance to people who can't afford it. The inhibiting factor in providing legal aid is that not all people know about legal aid institutions and the lack of legal education. The view of Islamic law on the provision of legal aid for underprivileged communities at the Legal Aid Institute (LBH) Pancaran Hati Cirebon is that it has become an order from Allah SWT in upholding Islamic law with the principles of justice, equality and mutual help, namely that everyone has the right to his or her rights and everyone equal status before the law. The implementation of providing legal aid to the poor is an application of the principle of mutual assistance in terms of goodness and piety. This act is a worship relationship between fellow creatures (hablum minannas) with the aim of benefiting the people.